2020
DOI: 10.3389/fphys.2020.00924
|View full text |Cite
|
Sign up to set email alerts
|

E-Liquid Containing a Mixture of Coconut, Vanilla, and Cookie Flavors Causes Cellular Senescence and Dysregulated Repair in Pulmonary Fibroblasts: Implications on Premature Aging

Abstract: Electronic cigarette (e-cig) usage has risen dramatically worldwide over the past decade. While they are touted as a safe alternative to cigarettes, recent studies indicate that high levels of nicotine and flavoring chemicals present in e-cigs may still cause adverse health effects. We hypothesized that an e-liquid containing a mixture of tobacco, coconut, vanilla, and cookie flavors would induce senescence and disrupt wound healing processes in pulmonary fibroblasts. To test this hypothesis, we exposed pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…In general, the use of a 1-5% tobacco flavor did not yield any marked differences in measurable outcomes of testis toxicity (El Golli et al, 2016b;Rahali et al, 2018) or hepatic function (El Golli et al, 2016a). Similar results were obtained in DNA damage and mitochondrial dysfunction with tobacco flavor (concentration not mentioned) (Espinoza-Derout et al, 2019), and pro-senescence phenotypes (Sundar et al, 2016;Jabba and Jordt, 2019;Lucas et al, 2020) FIGURE 2 | Cellular dysfunction by inhaled flavoring agents. Flavoring chemicals induced oxidative stress and inflammatory responses are associated with immune-responses via alterations in barrier tight junction dysfunction in the lung.…”
Section: Current Status On Flavor Induced Toxicology In Micesupporting
confidence: 52%
“…In general, the use of a 1-5% tobacco flavor did not yield any marked differences in measurable outcomes of testis toxicity (El Golli et al, 2016b;Rahali et al, 2018) or hepatic function (El Golli et al, 2016a). Similar results were obtained in DNA damage and mitochondrial dysfunction with tobacco flavor (concentration not mentioned) (Espinoza-Derout et al, 2019), and pro-senescence phenotypes (Sundar et al, 2016;Jabba and Jordt, 2019;Lucas et al, 2020) FIGURE 2 | Cellular dysfunction by inhaled flavoring agents. Flavoring chemicals induced oxidative stress and inflammatory responses are associated with immune-responses via alterations in barrier tight junction dysfunction in the lung.…”
Section: Current Status On Flavor Induced Toxicology In Micesupporting
confidence: 52%
“…Chemicals in EC products impair cell processes and induce inflammatory responses in multiple cell types. The concentrations of flavor chemicals and synthetic coolants in EC products are high enough to affect cell growth and morphology during acute exposure. In the current study, the cytotoxicity of Puff EC fluids in the MTT and NRU assays was significantly correlated with total chemical concentration and individual chemicals (nicotine, WS-3, WS-23, and ethyl maltol).…”
Section: Discussionmentioning
confidence: 99%
“…Electronic cigarettes (ECs), which contain nicotine, solvents, and flavor chemicals, continue to evolve and grow in popularity, especially among young adults. The popularity of fourth-generation EC products and their disposable spinoffs, especially among young users, has been attributed to flavored and “icy” fluids, usability, and device features that facilitate stealth use. EC fluids and aerosols generated from multiple devices contain higher concentrations of chemicals than used in other consumer products, such as foods, cosmetics, and medicines. ECs and their constituents are cytotoxic to cells, induce inflammatory responses, increase oxidative stress, cause cellular senescence, and negatively affect cell membrane channel potentials. Despite concern over the use of flavor chemicals in ECs, the chemicals used in EC fluids continue to change and are largely unregulated. Even though JUUL dominates the EC market with 63% of current sales, , projections show that disposables, such as Puff Bar, are likely to continue to increase their sales through 2028…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies point to the emerging evidence that cigarette menthol in may contribute to an increased risk for lung cancer by inhibiting the detoxification and clearance of the potent lung carcinogens (32,33). Another study on the direct exposure of e-liquid containing coconut, vanilla and cookie flavors showed that mixed flavored e-liquid caused changes observed in long time cigarette smokers by inducing inflammation, cytotoxicity, and inhibiting wound healing responses in pulmonary fibroblasts (34). A recent study by Abouassali et al showed in vitro using HL-1 cardiomyocytes that e-vapors containing flavoring aldehydes such as vanillin and cinnamaldehyde can compromise cardiac electrophysiological functions, leading to action potential instability and inducible ventricular arrhythmias (35).…”
Section: E-liquid: Composition and Health Effectsmentioning
confidence: 99%